Erythema dyschromicum perstans in a child following an enteroviral meningitis - Cláudia Raquel Ferrão de Melo; Mário Correia de Sá; Sónia Carvalho (Sociedade Brasileira de Dermatologia, 2017)
ABSTRACT A healthy 6-year-old boy presented with an erythematous macular exanthema, meningeal signs and fever, initially diagnosed with probable bacterial meningitis and treated with antibiotic and anti-inflammatory drugs. Enteroviral meningitis was confirmed, but the skin lesions continued to evolve and the patient was ultimately diagnosed with erythema dyschromicum perstans. The boy was followed during three years until the spontaneous resolution of the dermatosis.